Interview with anti-British freedom fighter and former Congress minister Pratap Chandra Chandra (88), interviewed by Kabir in Kolkata - Kabir, Shahriar.
Interview with anti-British freedom fighter and former Congress minister Pratap Chandra Chandra (88), interviewed by Kabir in Kolkata.